ASSET UTILIZATION OPTIMIZATION, LOCAL GOVERNMENT SUPPORT, ASSET MANAGEMENT PROFESSIONALISM TOWARDS INCREASING VILLAGE ORIGINAL INCOME - Erna Hendrawati (Jurnal Akuntansi, 2021)
This study aims to examine and analyze the effect of optimizing asset utilization, local government support, asset management professionalism on increasing Village Original Income (PA Desa). The research population is village officials in Menganti District, Gresik Regency, East Java. The questionnaire that can be obtained is 160 respondents. The data analysis techniques are validity test, reliability test, classical assumption test and multiple regression test. The results of the optimization of asset utilization and asset management professionalism affect village original income, while government support does not affect village original income. This can happen because village officials are aware that by optimizing asset utilization and managing assets professionally, they can increase the village's original income even though there is and no support from the government.